Identifying Molecular Chechkpoints for Adventitious Root Induction: Are We Ready to Fill the Gaps? - Abarca, Dolores (Frontiers in Plant Science, 2021)
The molecular mechanisms underlying adventitious rooting have been under study for the last decades. As new tools and resources became available, a comprehensive model connecting the processes and factors involved was developed. Separate phases that allow for specific analyses of individual checkpoints were well defined. Physiological approaches provided information on the importance of metabolic processes for activation of stem cell niches to form new root meristems. The study of plant hormones revealed sequential roles for cytokinin and auxin, dynamically interconnected and modulated by jasmonic acid and ethylene. The identification of genes specifying cell identity uncovered a network of transcriptional regulators that link hormonal control to cell fate respecification. Combined results from model plants and the study of recalcitrant species underscored the need to understand the limiting factors that determine adventitious rooting competence. The relevance of epigenetic control was emphasized by the identification of chromatin remodeling agents involved in the process. As different players are set in place and missing pieces become apparent, findings in related processes can be used to identify new candidates to complete the picture. Molecular knobs connecting the balance cell proliferation/differentiation to hormone signaling pathways or metabolic modulation of developmental programs can offer clues to unveil new elements in the dynamics of adventitious rooting regulatory networks. Mechanisms for cell non-autonomous signaling that are well characterized in related developmental processes can be further explored. Here we discuss possible candidates and approaches to address or elude the limitations that hinder propagation programs requiring adventitious rooting.